Health Literacy and Visual Inspection With Acetic Acid Screening Behavior Among Women of Reproductive Age in Pancoran Mas Community Health Center, Depok: A Cross-Sectional Study - Raden Roro Maulidya Arifianti Ningtyas; Nurul Huriah Astuti; Retno Mardhiati (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
Cervical cancer incidence has been increasing and has become an emerging threat to women’s health particularly in developing countries. Visual inspection with acetic acid (VIA) is a cost-effective screening method, however its utilization remains suboptimal. This study aimed to analyze the factors associated with women’s participation in VIA screening. An observational analytic study using a cross-sectional design was conducted among 152 women of reproductive age (30-50 years) in the Pancoran Mas Community Health Center area. Data were analyzed using the Chi-Square test and multiple logistic regression. Bivariate analysis revealed that attitudes, health literacy, perceived health belief model components (susceptibility, severity, benefits, barriers and self-efficacy), access to health services, support (from husband, families and community health workers) were significantly associated with VIA testing (p < 0.05). A multivariate analysis identified three significant factors: health literacy (OR = 11.203; 95% CI = 3.079-40.763), perceived susceptibility (OR = 3.943; 95% CI = 1.090-14.265), and perceived barriers (OR = 4.466; 95% CI = 1.358-14.687). Health literacy is the most dominant factor associated with VIA screening behavior. Notably, women with adequate health literacy were 11 times more likely to participate in screening. Enhancing screening participation can be achieved by fostering adequate health literacy through optimized health promotion targeting women of reproductive age. This strategy involves the distribution of educational media, such as informative leaflets and posters within the community health center area.